The Backward Clock, truth-tracking, and safety - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2015)
We present Backward Clock, an original counterexample to Robert Nozick’s truth-tracking analysis of propositional knowledge, which works differently from other putative counterexamples and avoids objections to which they are vulnerable. We then argue that four ways of analyzing knowledge in terms of safety, including Duncan Pritchard’s, cannot withstand Backward Clock either.